Enzymatic Decaffeination of Dampit Robusta Coffee (Coffea canephora) Using Crude Pineapple (Ananas comosus) Enzyme Extract with UV-Vis, FTIR, and Organoleptic Analysis - Swijayanti, Gusti Ayu Made Devta; Sairi, Rijal Alfayyed; Aisy, Fathia Rihhadatul; Febriana, Eka (Directorate of Research and Community Services, 2025)
This study developed a green decaffeination method for Dampit Robusta coffee using crude pineapple bromelain extract. A factorial design (enzyme concentration: 40-80%; time: 4-12 h) optimized the process, evaluated by UV-Vis spectrophotometry. The treatment with 80% enzyme for 12 hours reduced caffeine content by 95.8%. A multiple linear regression model (R² = 0.9404) confirmed the significant synergistic effect of concentration and time. FTIR spectroscopy revealed the mechanism, showing proteolytic alteration of the Amide I band (1637 cm⁻¹) in the enzymatic sample, absent in a commercial decaf. This indicates bromelain hydrolyzes bean proteins, facilitating caffeine diffusion. Furthermore, anomalous peaks (e.g., 2171 cm⁻¹) in the commercial sample suggested non-native residues, highlighting a purity advantage of the enzymatic method. Organoleptic analysis indicated a trade-off, where the most effective treatment compromised sensory attributes, while a moderate condition (60%, 4h) maintained acceptability. The work establishes a sustainable decaffeination framework and demonstrates FTIR's utility as a diagnostic tool for process verification and residue screening in food biotechnology.